Is hypoxia a cause or a consequence? The medico-legal considerations of neonatal encephalopathy and cerebral palsy - Yıldız Silahlı, Nicel; Akçakaya, Nihan Hande; Aslıyüksek, Hızır; Yılmaz, Muhammed Emre; Madazlı, Rıza; Celkan, Tülin Tiraje (Romanian Legal Medicine Society, 2022)
Neonatal encephalopathy (NE) occurs in the first month after birth of infants and progresses with seizures, respiratory depression and hypotonia. NE is multifactorial, however hypoxia is the first considered cause. Our study aims to discuss medicolegal processes behind the etiological and clinical features of NE and cerebral palsy (CP) over cases evaluated by the specialized board of malpractice of the Council of Forensic Medicine. The 130 cases in the judicial process claimed to be from lack of oxygen at birth, were evaluated retrospectively. The cases were categorized into two groups as evidenced with hypoxic-ischemic encephalopathy (HIE) and not evaluated evidence with HIE, by using blood gas evaluations and brain MRI findings. All risk factors related to labor, resuscitation, intubation, and referral to other NICUs, and presence of seizure were documented in both groups. We found no evidence of intrapartum hypoxia in about 70% of NE and it is suggesting that the causes of NE may have started in the antepartum period. It is necessary to focus on other inherent diseases that play a role in the etiology in medicolegal process, as well as investigate the presence of hypoxia and whether the correct intervention is made.
Keywords: Cerebral Palsy; Hypoxic Ischemic Encephalopathy; Malpractice; Neonatal Encephalopathy; Rare Diseases